Perbandingan Hasil Biometri dan Tajam Penglihatan pada Katarak Anak, Sebelum dan Sesudah Operasi Katarak - Uirianto, Meiliana Angeline; Umboh, Anne; Rares, Laya; Witjaksana, Riani (Jurnal Biomedika dan Kesehatan, 2025)
Background Lens disorders in pediatrics include cataracts and abnormalities in the shape, size, and location of the lens. These abnormalities are a significant source of visual impairment in children. Cataracts are responsible for nearly 10% of all childhood vision loss worldwide. Cataracts in children cause over one million cases of Blindness among Asian children. The purpose of this study is to analyze the differences in axial length (AL)—corneal curvature, and best-corrected visual acuity (BCVA) before and after surgery in pediatric cataract eyes. Methods This study used a comparative experimental analytical research design with a Pretest-Posttest on a single group without control, utilizing ocular biometry instruments and BCVA examination in pediatric cataract eyes before and after surgery. Results The BCVA and AL in 8 children showed significant differences. The average BCVA with logMAR decreased from 1.98 to 1.36 one month after surgery, with a paired t-test yielding a t-value of 2.595 and p-value of 0.018 < 0.05. Moreover, the initial BCVA average of 1.98 improved to 0.79 three months after surgery, with a t-value of 5.574 and a p-value of 0.001 (< 0.05). As for the AL, it increased from 22.21 mm to 22.57 mm one month after surgery, with a t-value of -2.475 and p-value of 0.021 < 0.05. Furthermore, the initial AL average of 22.21 mm increased to 22.75 mm three months after surgery, with a t-value of -4.375 and p-value of 0.003 < 0.05. Conclusions There were significant differences in BCVA and AL in the sample before pediatric cataract surgery, as well as one and three months after the surgery.